Comparative Proteomic Analysis of Paulownia fortunei Response to Phytoplasma Infection with Dimethyl Sulfate Treatment - Zhen Wei; Zhe Wang; Xiaoyu Li; Zhenli Zhao; Minjie Deng; Yanpeng Dong; Xibing Cao; Guoqiang Fan (International Journal of Genomics)
Paulownia fortunei is a widely cultivated economic forest tree species that is susceptible to infection with phytoplasma, resulting in Paulownia witches’ broom (PaWB) disease. Diseased P. fortunei is characterized by stunted growth, witches’ broom, shortened internodes, and etiolated and smaller leaves. To understand the molecular mechanism of its pathogenesis, we applied isobaric tags for relative and absolute quantitation (iTRAQ) and liquid chromatography coupled with tandem mass spectrometry approaches to study changes in the proteomes of healthy P. fortunei, PaWB-infected P. fortunei, and PaWB-infected P. fortunei treated with 15 mg·L−1 or 75 mg·L−1 dimethyl sulfate. We identified 2969 proteins and 104 and 32 differentially abundant proteins that were phytoplasma infection responsive and dimethyl sulfate responsive, respectively. Based on our analysis of the different proteomes, 27 PaWB-related proteins were identified. The protein-protein interactions of these 27 proteins were analyzed and classified into four groups (photosynthesis-related, energy-related, ribosome-related, and individual proteins). These PaWB-related proteins may help in developing a deeper understanding of how PaWB affects the morphological characteristics of P. fortunei and further establish the mechanisms involved in the response of P. fortunei to phytoplasma.